Discusses the Application of Art Design Concepts in Fashion Brand Shaping - Dong Meiling; Chen Yu (SHS Web of Conferences, 2023)
Clothing is a creation in the process of human survival and development. With the continuous development of the economy and the improvement of human living standards, the process of historical evolution is accelerating. The concept of clothing art design is no longer limited to practical functions, but extends to abstract functions such as aesthetics and artistic sense of clothing. This also promotes the expansion of the connotation of clothing art design concept, injects new soul into the shaping of clothing brands, and creates conditions for the diversified development of clothing brands.The article focuses on two directions: brand image shaping and brand culture shaping, and deeply analyzes the new trend of clothing consumption in the current era. It introduces the use of art design concepts, attempts to explore the shaping of clothing enterprise brand image and brand culture under art design concepts, and ultimately verifies the broad application prospects of art design concepts in clothing brand shaping.